Playing with the diary: how crafting a multimodal and sensory diary can have a positive impact on teacher wellbeing. Issue 1 (2nd January 2022) - Kelly, Lucy
ABSTRACT: This article uses the outcome of a small-scale research project – the 'Diary Toolkit' (DT) – to explore the creative process of crafting a multimodal, sensory diary as a positive tool for teacher wellbeing. In an educational climate facing the repercussions of the COVID-19 pandemic, the DT offered an epiphanic space for teachers in England, helping them navigate their way through this highly emotional and anxious time. Indeed, against the backdrop of COVID, a hidden pandemic has arisen: a decline in teachers' mental health and wellbeing. The article situates the DT within the field of reflective practice as a creative approach, arguing that in addition to supporting teaching and learning, it can also help teacher wellbeing. To demonstrate this, some key findings from the 'Reimagining the Diary' (2018) project are used, focusing, in particular, on those around choice/creativity, and structure/parameters. The article concludes by stating that the creative process of crafting a sensory and multimodal diary gives teachers the healing and nurturing space currently needed, as well as an opportunity to represent their wellbeing in multiple ways so that they can flourish inside and outside the classroom.